2023
DOI: 10.1021/acs.joc.2c02507
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Potential for Exploring Electron Delocalization in Infinitenes, Circulenes, and Nanobelts

Abstract: The π-conjugation, aromaticity, and stability of the newly synthesized 12-infinitene and of other infinitenes comprising 8-, 10-, 14-, and 16-arene rings are investigated using density functional theory. The π-electron delocalization and aromatic character rooted in infinitenes are quantified in terms of molecular electrostatic potential (MESP) topology. Structurally, the infinitene bears a close resemblance of its helically twisted structure to the infinity symbol. The MESP topology shows that infinitene poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…X-ray crystal structure analysis has shown that the combined lamellar and herringbone-like packing structure introduced three-dimensional electronic interactions caused by the infinity shape. Since this report, fascinating properties of infinitene have been predicted. Wu and Isobe et al synthesized a twisted CNB in 2021 and a fused [5]­helicene dimer in 2023 , as a related molecule of infinitene. In addition to aromatic hydrocarbon-based CNBs, heteroatom-embedded CNBs have also been reported. In 2019, Tanaka et al synthesized the first oxygen-embedded CNB by rhodium-catalyzed alkyne cyclotrimerization .…”
Section: Synthesis Of Cnbs and Related Aromatic Beltsmentioning
confidence: 98%
“…X-ray crystal structure analysis has shown that the combined lamellar and herringbone-like packing structure introduced three-dimensional electronic interactions caused by the infinity shape. Since this report, fascinating properties of infinitene have been predicted. Wu and Isobe et al synthesized a twisted CNB in 2021 and a fused [5]­helicene dimer in 2023 , as a related molecule of infinitene. In addition to aromatic hydrocarbon-based CNBs, heteroatom-embedded CNBs have also been reported. In 2019, Tanaka et al synthesized the first oxygen-embedded CNB by rhodium-catalyzed alkyne cyclotrimerization .…”
Section: Synthesis Of Cnbs and Related Aromatic Beltsmentioning
confidence: 98%